2008
DOI: 10.2478/v10102-010-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of the severity of asphyxia in term newborns using parameters of blood count

Abstract: Acute perinatal asphyxia is a major cause of death and neurological injury in newborn infants. Severe asphyxia can occur in infants around the time of birth for several reasons. The aim of our study was to find the most sensitive, easily obtainable and fast assessable parameter of the presence and quantification of asphyxia.In our study 39 term newborns (15 healthy term newborns and 24 asphyxial term newborns), from vaginal deliveries admitted within 24 hours of life were monitored and parameters of blood coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…cesarean delivery could avert intrapartum fetal trauma and asphyxia and allow timed delivery to assure readiness of neonatal intensive care resources. Asphyxia can lead to changes in blood count parameters (9) and probably in RBC folate concentration levels as confi rmed by Mi et al (29) as well as by the results of our study. A lot of retrospective and observational studies do not support routine cesarean delivery for all early preterm infants.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…cesarean delivery could avert intrapartum fetal trauma and asphyxia and allow timed delivery to assure readiness of neonatal intensive care resources. Asphyxia can lead to changes in blood count parameters (9) and probably in RBC folate concentration levels as confi rmed by Mi et al (29) as well as by the results of our study. A lot of retrospective and observational studies do not support routine cesarean delivery for all early preterm infants.…”
Section: Discussionsupporting
confidence: 76%
“…RBC folate concentration levels were not impacted by gender in our study. Laboratory fi ndings associated with perinatal asphyxia pointed out the changes in blood count parameters such as erythrocyte count and hemoglobin and hematocrit values (9). On the other hand the chronic long-term intermittent hypoxia leads to an increase in haematocrit and whole blood viscosity (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was supported by Darkhaneh et al (6) . However Brucknerova et al (3) reported lower hemoglobin values in newborns in case group (p value=0.01).…”
Section: Discussion:-mentioning
confidence: 99%
“…The parameters used for predicting or defining asphyxia include Apgar score, acidemia of the umbilical cord artery, fetal heart monitoring, patterns of heartbeat, pH metry of the blood of fetal head, increased level of serum erythropoietin, and presence of meconium in amniotic fluid (3) However, to date no single marker of perinatal asphyxia has shown good predictive efficacy and only a combination of various indices can help in an early diagnosis of perinatal asphyxia. Recently, the count of umbilical cord NRBC for every 100 white blood cells has been introduced as a marker of perinatal asphyxia (4) .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%